Orientation and Mobility Skills of Ninth-Grade Students With Visual Impairments at SKH Bhakti Luhur - , Yasinta Lesu Dares; Lilis Suwandari, (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Orientation and mobility skills need to be taught to blind children, especially totally blind children, because through orientation and mobility they can increase their independence without always having to depend on others, move and change places safely and efficiently, and utilize other senses that still function. The purpose of this study was to obtain an overview of the abilities and difficulties of blind children, the atmosphere during orientation and mobility learning, and the implementation of orientation and mobility learning. This study applied a descriptive method with a qualitative approach, and data were collected through observation, interviews, and documentation studies. Based on the results of the study, it is known that totally blind ninth-grade children can participate in orientation and mobility learning with the help of teachers, starting from learning about orientation and mobility, learning about assistive devices and orientation and mobility techniques, learning about and describing the school environment, and learning, describing, and practicing the trailing technique. The difficulties faced by totally blind children during orientation and mobility learning were when practicing orientation and mobility in a large environment because there were no tactile cues that could be applied for orientation and mobility, as well as difficulties practicing orientation and mobility on stairs due to fear of falling. Teachers carry out initial, core, and closing activities during learning. The conclusions of this study form the basis for researchers to provide recommendations to school principals and teachers to optimize orientation and mobility learning for totally blind children on a regular basis. Keywords: Orientation and Mobility, Visual Impairments Abstrak: Keterampilan orientasi dan mobilitas perlu diajarkan kepada anak-anak tunanetra, terutama anak-anak tunanetra total, karena melalui orientasi dan mobilitas mereka dapat meningkatkan kemandirian tanpa selalu bergantung pada orang lain, bergerak dan berpindah tempat dengan aman dan efisien, serta memanfaatkan indra lain yang masih berfungsi. Tujuan penelitian ini adalah untuk memperoleh gambaran tentang kemampuan dan kesulitan anak-anak tunanetra, suasana selama pembelajaran orientasi dan mobilitas, serta implementasi pembelajaran orientasi dan mobilitas. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif, dan data dikumpulkan melalui observasi, wawancara, dan studi dokumentasi. Berdasarkan hasil penelitian, diketahui bahwa anak-anak buta total kelas sembilan dapat berpartisipasi dalam pembelajaran orientasi dan mobilitas dengan bantuan guru, mulai dari belajar tentang orientasi dan mobilitas, belajar tentang alat bantu dan teknik orientasi dan mobilitas, belajar tentang dan mendeskripsikan lingkungan sekolah, serta belajar, mendeskripsikan, dan mempraktikkan teknik trailing. Kesulitan yang dihadapi oleh anak-anak tunanetra total selama pembelajaran orientasi dan mobilitas adalah saat mempraktikkan orientasi dan mobilitas di lingkungan yang luas karena tidak ada petunjuk taktil yang dapat diterapkan untuk orientasi dan mobilitas, serta kesulitan mempraktikkan orientasi dan mobilitas di tangga karena takut jatuh. Guru melaksanakan kegiatan awal, inti, dan penutup selama pembelajaran. Kesimpulan dari penelitian ini menjadi dasar bagi peneliti untuk memberikan rekomendasi kepada kepala sekolah dan guru untuk mengoptimalkan pembelajaran orientasi dan mobilitas bagi anak-anak tunanetra total secara rutin. Kata kunci: Orientasi dan Mobilitas, Tunanetra Total.